Online examination for takaful basic examination – a license to practice certificate: a Malaysian case - Jamil Ahmad; Bibi Nabi Ahmad Khan; Santhi Raghavan; Tuan Fatma Tuan Sulaiman (2019)
The purpose of this study is to examine the extent of effectiveness of the online examination using electronic learning management system (e-LMS) services in the Malaysian Takaful sector for Takaful Basic Examination (TBE). TBE is conducted through online examination which is a web-based examination system (ES). The TBE is an entry qualification for all those who intend to become registered takaful agents in the financial services industry promoting takaful products and services. The term Takaful refers to the concept of Islamic insurance based on mutual cooperation, where both risks and funds are shared between the insured and insurer. TBE is a mandatory license-to-practice qualification to enhance the competency and professionalism of takaful agents. It is also an induction for individuals who intend to pursue a career in Takaful. The study also aims to address issues concerning quality of services by focusing on the following: ease of use, information security and reliability and its role in influencing customer adoption of electronic services, as well as the mechanisms of monitoring and control over these services. The research employed the analytic and descriptive methodology, by collecting secondary data on candidates sitting for the examination. This was then compared to the passing rate from the year 2012 until 2016. The findings show that online examinations have succeeded in attaining significant customer satisfaction by improving electronic services, facilitating electronic transactions, improving processing performance and enhancing the specifications of electronic services. In addition, the Takaful institutions have achieved effective communication with their customers as well as speeding up of applications. However, there is an absence of awareness and guidance for candidates about the e-examination system. The results of this research led to some recommendations to improve the electronic services provided by Takaful institutions in order to enhance customer and institution’s satisfaction. (Abstract by authors)